Making the Planet More Habitable: Business Perspectives for Social Economy - Mendes Pekdemir, Isil (Istanbul University Press, 2023)
It would be better to make our planet more habitable for future generations. That way, every human being would have fair access to the goods and services they need in order to sustain and survive. Unfortunately, due to rapid growth, industrialization, urbanization, and other developments, human beings around the world have faced many social and environmental issues which have increased gradually, such as global warming, environmental pollution, endangerment of biological diversity and ecosystems, rapid consumption of natural resources, food security, healthy water shortage, and many others. These are global problems that concern all of humanity. In line with globalization and environmental changes, profit-oriented business enterprises should fulfill their social responsibilities while continuing their economic activities. It is necessary for business enterprises to assist in increasing the quality of life of societies, contribute to economic development, provide social benefits, protect nature, consider the needs of future generations while meeting today's needs, and contribute to the solution of social and environmental problems. It has become imperative for for-profit and not-for-profit businesses to consider practices that would sustain life and make our planet more livable in the future. This book focuses on sustainability, social development, solidarity, social justice, social welfare, accessing goods and services, and meeting the needs of future generations. All of this relates to an economic model: the social economy model. Under the social economy model, the need for social goals would be prioritized. While trying to achieve a balance between the economic, social, and natural environmental elements of the enterprises in the context of sustainability, business enterprises would have different business perspectives when considering the social economy, particularly for social and environmental issues.